UV-Irradiated Photocatalytic Degradation of Nitrobenzene by Titania Binding on Quartz Tube - Thou-Jen Whang; Mu-Tao Hsieh; Tjaun-En Shi; Chun-Hsiung Kuei (International Journal of Photoenergy)
A new method for UV-irradiated degradation of nitrobenzene by titania photocatalysts was proposed, titania nanoparticles were coated on a quartz tube through the introduction of tetraethyl orthosilicate into the matrix. The dependence of nitrobenzene photodegradation on pH, temperature, concentration, and air feeding was discussed, and the physical properties such as the activation energy, entropy, enthalpy, adsorption constant, and rate constant were acquired by conducting the reactions in a variety of experimental conditions. The optimum efficiency of the photodegradation with the nitrobenzene residue as low as 8.8% was achieved according to the experimental conditions indicated. The photodegradation pathways were also investigated through HPLC, GC/MS, ion chromatography (IC), and chemical oxygen demand (COD) analyses.